2011
DOI: 10.1007/s00125-011-2115-7
|View full text |Cite
|
Sign up to set email alerts
|

Hyperaminoacidaemia at postprandial levels does not modulate glucose metabolism in type 2 diabetes mellitus

Abstract: Postprandial circulating amino acid concentrations do not worsen the already attenuated glucose disposal in hyperglycaemic type 2 diabetic men, and cell-signalling events are consistent with this. Our results do not support recommendations to restrict dietary protein in type 2 diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 42 publications
2
7
0
Order By: Relevance
“…Our data on plasma BCAA showed that when leucine gavage is administered prior to ITT, the elevated plasma BCAA is rapidly brought back to normal, consistent with the idea that in lean rats, these amino acids do not impair insulin sensitivity, as others have shown (Bassil et al. ). Obviously this measure reflects whole body average and does not allow identification of tissue‐specific effect.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Our data on plasma BCAA showed that when leucine gavage is administered prior to ITT, the elevated plasma BCAA is rapidly brought back to normal, consistent with the idea that in lean rats, these amino acids do not impair insulin sensitivity, as others have shown (Bassil et al. ). Obviously this measure reflects whole body average and does not allow identification of tissue‐specific effect.…”
Section: Discussionsupporting
confidence: 89%
“…impaired insulin regulation of protein metabolism, which would lead to increased availability of free (glucogenic) AA, to the increased gluconeogenesis observed in insulinresistant individuals (Chevalier et al 2006). Our data on plasma BCAA showed that when leucine gavage is administered prior to ITT, the elevated plasma BCAA is rapidly brought back to normal, consistent with the idea that in lean rats, these amino acids do not impair insulin sensitivity, as others have shown (Bassil et al 2011). Obviously this measure reflects whole body average and does not allow identification of tissue-specific effect.…”
Section: Discussionsupporting
confidence: 89%
“…These authors have also reported that the anabolic response of skeletal muscle protein metabolism to insulin infusion is very similar in diabetic and healthy subjects [128,129]. On the other hand, other authors have described that insulin resistance is involved in protein metabolism [130,131]. More specifically, they have shown that, upon insulin infusion, type 2 diabetic subjects do not display increased protein anabolism or inhibition of protein catabolism.…”
Section: Protein Metabolism and Muscle Mass In Type 2 Diabetes Mellitmentioning
confidence: 71%
“…We showed that amino acids can overcome the insulin resistance of protein metabolism through their anabolic action (Bassil et al, 2011a) without further impairing glucose metabolism in obese middle-aged men with type 2 diabetes (Bassil et al, 2011b). Moreover, a recent systematic review and meta-analysis of 20 randomized controlled trials investigating dietary approaches in the management of type 2 diabetes indicated that high-protein diets are among the few approaches that are effective in improving glycemic control (Ajala et al, 2013).…”
Section: Discussionmentioning
confidence: 99%